Gestão de recursos humanos e organizações substantivas: um estudo comparativo - Reis, Fabiano Alves dos (2017)
Purpose - The main objective of this research is to verify if, even in NGOs with large numbers of employees and funders, the isonomic characteristics are maintained, from the point of view of human resources practices. Methodology - The research presented here is based on the social constructivist conception used by Creswell (2010), according to which "social constructivists defend assumptions that individuals seek to understand the world in which they live and work" (CRESWELL, 2010, 31). In addition to the previous point, social constructivism can also be called a qualitative or interpretive paradigm, hermeneutic, naturalistic and qualitative (COUTINHO, 2014). Interviews were conducted with seven NGO staff and ten staff from a private organization to verify the substantive rationale within each organization. Eight variables were analyzed based on the responses of the 17 interviewees. At the end of the analysis, it was possible to compare the two companies and to verify which of the organizations presents the highest intensity of substantive rationality. Findings - After analyzing all variables studied in the research, in general the company Alpha was framed at the high level of the continuum of substantive intensity, while the NGO Beta remained at the low level of the same continuum. Research limitations - Because it is a qualitative research, it was not possible to use a large number of organizations, be they private or social. Therefore, it is not possible to say that its results are valid for all organizations. As the organization that is the object of this research has a structure that differs it from other Brazilian NGOs in terms of size and financing, we can not extrapolate the results obtained for other NGOs. Practical implication - We hope that this research contributes to the studies on the management of NGOs, which today are still scarce in the Brazilian academic literature. Moreover, even if timidly, we expect this field research to fill in part of the gap left by theorists about substantive organizations, advancing to the heuristic discussions on the subject. Originality - From the research done, no other studies have been found that study NGOs and substantive organizations from the human resources department point of view.